Dysphagia in Amyotrophic Lateral Sclerosis: Impact on Patient Behavior, Diet Adaptation, and Riluzole Management - Onesti, Emanuela; Schettino, Ilenia; Gori, Maria Cristina; Frasca, Vittorio; Ceccanti, Marco; Cambieri, Chiara; Ruoppolo, Giovanni; Inghilleri, Maurizio (Frontiers in Neurology, 2017)
This retrospective study aimed to investigate the clinical features associated with deteriorated swallow in amyotrophic lateral sclerosis (ALS) patients with spinal and bulbar onset, describe the modification of diet and liquid intake, and assess the impact of dysphagia on the use of riluzole. One hundred forty-five patients were observed periodically every three-six months. They underwent routinely Fiberoptic Endoscopic Evaluation of Swallowing (FEES) and spirometry; dysphagia severity was classified according to the Penetration Aspiration Scale (PAS) and the Pooling score (P score) integrated with other parameters such as sensation, collaboration and age (P-SCA score). During a mean follow-up period of about two years, the % of ALS patients suffering from dysphagia increased to 85% (rising from 35% to 73% in patients with spinal onset, and from 95% to 98% in those with bulbar onset). 8% of patients with dysphagia by FEES did not perceive the disorder. The frequency of normal and semi-solid diets decreased over time, while that of pureed diets and percutaneous endoscopic gastrostomy (PEG) prescription increased. 44% of dysphagic patients refused thickeners or PEG. A significant difference was observed in the mortality rate between patients untreated with riluzole and patients treated with riluzole oral suspension (p<0.05). Disease duration mainly impacted on the frequency of dysphagia in spinal onset patients, appearing very early in those with bulbar onset. Riluzole oral suspension would allow the safe administration in dysphagic ALS patients to avoid tablet crushing and consequent dispersion in food, common practices that are inconsistent with the safe and effective use of the drug.